2018
DOI: 10.1017/jog.2018.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between a multi-variate nudging method and the ensemble Kalman filter for sea-ice data assimilation

Abstract: Increasing ship traffic and human activity in the Arctic has led to a growing demand for accurate Arctic weather forecast. High-quality forecasts obtained by models are dependent on accurate initial states achieved by assimilation of observations. In this study, a multi-variate nudging (MVN) method for assimilation of sea-ice variables is introduced. The MVN assimilation method includes procedures for multivariate update of sea-ice volume and concentration, and for extrapolation of observational information sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 40 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…The effect is much stronger for the SMOS rim SIT assimilation, indicating that a large portion of the original sea-ice volume overestimation is located in the MIZ. This is a consequence of too much ice in the control model, causing the observed MIZ to be located deeper in the Arctic compared to the model, as noted by Fritzner et al (2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect is much stronger for the SMOS rim SIT assimilation, indicating that a large portion of the original sea-ice volume overestimation is located in the MIZ. This is a consequence of too much ice in the control model, causing the observed MIZ to be located deeper in the Arctic compared to the model, as noted by Fritzner et al (2018).…”
Section: Discussionmentioning
confidence: 97%
“…In general, similarly to that found by Yang et al (2014) the SMOS observations were found to have a relatively small impact on the SIC and the SIT far from the ice edge. Fritzner et al (2018) assimilated SMOS observations into a stand-alone sea-ice model with the EnKF. This study showed that, due to the correlation between SIC and SIT, the SMOS observations were found to have a positive effect on the modelled SIC.…”
Section: Introductionmentioning
confidence: 99%
“…The effect is much stronger for the SMOS rim SIT assimilation, indicating that a large portion of the original sea-ice volume overestimation is located in the MIZ. This is a consequence of too much ice in the control model causing the observed MIZ to be located deeper into the Arctic as compared to the model, as noted by Fritzner et al (2018).…”
Section: Maymentioning
confidence: 98%
“…(Caya et al, 2010;K. Wang et al, 2013;Sakov et al, 2012;Buehner et al, 2013;Yang et al, 2014;Posey et al, 2015;Shlyaeva et al, 2016;Xie et al, 2016;Mu et al, 2018;Fritzner et al, 2018Fritzner et al, , 2019. Common for many of the Arctic sea-ice models used in these studies is that the model resolution is typically coarse, on the order of 10-20 km.…”
mentioning
confidence: 99%
“…(Lisaeter et al, 2003;Sakov et al, 2012;K. Wang et al, 2013;Buehner et al, 2013;Posey et al, 2015;Fritzner et al, 2018Fritzner et al, , 2019. Sea-ice concentration (SIC) is by far the most used variable in sea-ice data assimilation studies, however other types of observations have become available in recent years.…”
mentioning
confidence: 99%